Comparative genomics of the extremophile Cryomyces antarcticus and other psychrophilic Dothideomycetes - Gomez-Gutierrrez, Sandra V.; Sic-Hernandez, Wily R.; Haridas, Sajeet; LaButti, Kurt; Eichenberger, Joanne; Kaur, Navneet; Lipzen, Anna; Barry, Kerrie; Goodwin, Stephen B.; Gribskov, Michael; Grigoriev, Igor V. (Frontiers in Fungal Biology, 2024)
Over a billion years of fungal evolution has enabled representatives of this kingdom to populate almost all parts of planet Earth and to adapt to some of its most uninhabitable environments including extremes of temperature, salinity, pH, water, light, or other sources of radiation.Cryomyces antarcticus is an endolithic fungus that inhabits rock outcrops in Antarctica. It survives extremes of cold, humidity and solar radiation in one of the least habitable environments on Earth. This fungus is unusual because it produces heavily melanized, meristematic growth and is thought to be haploid and asexual. Due to its growth in the most extreme environment, it has been suggested as an organism that could survive on Mars.However, the mechanisms it uses to achieve its extremophilic nature are not known.Comparative genomics can provide clues to the processes underlying biological diversity, evolution, and adaptation. This effort has been greatly facilitated by the 1000 Fungal Genomes project and the JGI MycoCosm portal where sequenced genomes have been assembled into phylogenetic and ecological groups representing different projects, lifestyles, ecologies, and evolutionary histories. Comparative genomics within and between these groups provides insights into fungal adaptations, for example to extreme environmental conditions. Here, we analyze two Cryomyces genomes in the context of additional psychrophilic fungi, as well as nonpsychrophilic fungi with diverse lifestyles selected from the MycoCosm database. This analysis identifies families of genes that are expanded and contracted in Cryomyces and other psychrophiles and may explain their extremophilic lifestyle. Higher GC contents of genes and of bases in the third positions of codons may help to stabilize DNA under extreme conditions. Numerous smaller contigs in C. antarcticus suggest the presence of an alternative haplotype that could indicate the sequenced isolate is diploid or dikaryotic. These analyses provide a first step to unraveling the secrets of the extreme lifestyle of C. antarcticus.